2019
DOI: 10.1111/febs.14987
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of Trypanosoma brucei hypoxanthine – guanine – xanthine phosphoribosyltransferase in complex with IMP, GMP and XMP

Abstract: The 6‐oxopurine phosphoribosyltransferases (PRTs) are drug targets for the treatment of parasitic diseases. This is due to the fact that parasites are auxotrophic for the 6‐oxopurine bases relying on salvage enzymes for the synthesis of their 6‐oxopurine nucleoside monophosphates. In Trypanosoma brucei, the parasite that is the aetiological agent for sleeping sickness, there are three 6‐oxopurine PRT isoforms. Two are specific for hypoxanthine and guanine, whilst the third, characterized here, uses all three n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…This dependency represents a potentially promising ground for the discovery of anti-parasitic compounds with a purine-based scaffold. Indeed, we showed that potent 6-oxopurine acyclic nucleoside phosphonates (ANPs) inhibit 6-oxopurine phosphoribosyl transferases in vitro as well as possess strong cytotoxic effects on T. brucei bloodstream form cells 6 , 17 , 18 . Using our experience with this system, we designed new selective adenine-based ANPs and evaluated their activity in vitro and in T. brucei culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dependency represents a potentially promising ground for the discovery of anti-parasitic compounds with a purine-based scaffold. Indeed, we showed that potent 6-oxopurine acyclic nucleoside phosphonates (ANPs) inhibit 6-oxopurine phosphoribosyl transferases in vitro as well as possess strong cytotoxic effects on T. brucei bloodstream form cells 6 , 17 , 18 . Using our experience with this system, we designed new selective adenine-based ANPs and evaluated their activity in vitro and in T. brucei culture.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we determined the crystal structures of two T. brucei PSP enzymes, 6-oxopurine PRTases, in the complex with several ANPs, and showed that the prodrugs of the selected inhibitors possess strong anti-trypanosomal activity in the cell-based assay 6 , 17 , 18 . Inspired by these results, here we focused on the 6-aminopurine salvage route, which is linked to the 6-oxopurine pathway via an AMP deaminase that converts AMP to IMP (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The structure was solved by molecular replacement using the program PHASER within PHENIX 1.18.2 . For human HGPRT, the starting model was PDB code: 5HIA; for Tbr HGPRT1, PDB code: 5JV5; and for Tbr HGXPRT, PDB code: 6AQO . Subsequent refinement and model building were done with PHENIX 1.18.2 and COOT 0.8.9.2 .…”
Section: Methodsmentioning
confidence: 99%
“…18.2. 40 For human HGPRT, the starting model was PDB code: 5HIA; 18 for TbrHGPRT1, PDB code: 5JV5; 41 and for TbrHGXPRT, PDB code: 6AQO. 9 Subsequent refinement and model building were done with PHENIX 1.…”
Section: (Boc) Ms (Esi + ) M/z = 454 [M + H] +mentioning
confidence: 99%
“…The authors proposed the role of the conserved water molecule as an adapter to facilitate binding of both XMP and GMP to HGXPRT. 69 This water plays no role in the binding of Hx, as its C2-carbon cannot form hydrogen bonds but instead makes hydrophobic interactions with Phe204 (a Leu in TcHGPRT, the last of the three substitutions observed between the T. cruzi isoforms). Binding of XMP, GMP, and IMP to the active sites of TbbHGXPRT is highly conserved.…”
Section: Viscosity Studies and The Determination Of Rate-limitingmentioning
confidence: 99%